Assessment of genotoxic effect of Ocimum basilicum L. and Linalool (Research, Society and Development, 2020)
Ocimum basilicum belongs to the Lamiaceae family, is popularly known as basil and can be found in several regions of the world, being the monoterpene Linalol or the main component of the essential oil of Ocimum basilicum L. Medicinally it is considered powerful antiseptic, carminative, digestive, insecticide and analgesic, besides having proven antibacterial, antifungal and antiviral activities. Knowing that evaluating the genotoxic activity of medicinal plants is extremely important as one of the stages of the toxicity study, this study aimed to analyze the genotoxic effect of basil essential oil and its active ingredient linalool. The micronucleus test on peripheral blood cells was used in the study for activities. Groups of three mices males and three females received, by gavage, the compounds in dose of 100 and 200 mg/kg of animal weight. The negative control group received only the dispersant of the sample (distilled water) and positive control received Cyclophosphamide 50 mg/kg of animal weight. Twenty-four hours after treatment, the animals were sacrificed, blood was collected from the caudal vein and made a smear on the slide. The obtained results showed the absence of genotoxic effect of tested compounds. Further studies of toxicity need to be made to the use of this plant in the treatment of diseases to be stimulated.